Factors influencing women's access to the maternity waiting home in rural Southwest Ethiopia: a qualitative exploration - Kindie Mitiku Kebede; Kebadnew Mulatu Mihrete (BMC, 2020)
Abstract Background Maternity Waiting Homes (MWHs) have been advocated to improve the utilization of skilled birth attendants. Nevertheless, delivery attended by skilled personnel is low in Ethiopia and may indicate that the utilization of MWH is also low. The aim of this study is to explore the factors influencing women's access to the MWHs in rural Southwest Ethiopia. Methods Qualitative data were collected through focus group discussions with MWHs users and in-depth interviews with MWHs non-users, health extension workers and the clinicians. Four focus group discussions and 18 in-depth interviews were conducted between May 1 and June 1, 2017. Furthermore, observations were made to assess the availability of basic facilities at selected MWHs. Data were thematically analyzed using NVivo version 7. The concept of access defined by Thiede et al was applied to guide the analysis. Results Women had interest on MWHs and are aware of the existence of MWHs in their immediate vicinity. Health information disseminations and referral linkages by frontline health workers enabled women to timely access the MWHs. However, Women didn't understand the aims and benefits of MWHs. At the facility level, there were attempts to improve the acceptability of MWHs by allowing women to choose their delivery positions. But, participants claimed lack of privacy and presence of disrespectful care. Physical barriers (long distance, unavailability of transport options & unfavorable roads) were considered as potential problems for women residing in remote areas. MWH users mentioned absences of sufficient basic facilities, poor quality and varieties of food. Because of insufficient facilities, the cost of living was high for most users. The communities try to overcome the indirect costs through contributions in-kind and in-cash. Conclusions The factors influencing women's access to the MWHs were structural and individual and resonate with Thiede et al. dimensions of access. A better understanding of which factors are most influential in preventing women's access to the MWHs in rural Southwest Ethiopia is needed to appropriately target interventions.